1976
DOI: 10.1677/joe.0.0690193
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Luteinizing Hormone and Progesterone in the Adult Female Pig During the Oestrous Cycle, Late Pregnancy and Lactation, and After Ovariectomy and Pentobarbitone Treatment

Abstract: In a series of experiments on female miniature pigs, the pattern of plasma LH and progesterone levels during the oestrous cycle, late pregnancy and lactation and after ovariectomy were characterized, and the effect of pentobarbitone treatment was tested. The preovulatory surge of LH occurred in seven out of eight animals between 00.00 and 12.0 h on day 0 of the oestrous cycle (day 1 of standing heat). Plasma progesterone strated to decline 8 days before oestrus and reached its lowest value 5 days before the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
65
1

Year Published

1979
1979
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(77 citation statements)
references
References 0 publications
11
65
1
Order By: Relevance
“…The pattern of LH was similar to that previously observed around the time of ovulation [4,18,19,21]. The timing of LH surge relative to the onset of oestrus and ovulation was the same as that obtained by others [6,15,27].…”
Section: Discussionsupporting
confidence: 87%
“…The pattern of LH was similar to that previously observed around the time of ovulation [4,18,19,21]. The timing of LH surge relative to the onset of oestrus and ovulation was the same as that obtained by others [6,15,27].…”
Section: Discussionsupporting
confidence: 87%
“…The hypophyseal luteotrophic factor had been suggested long ago to be LH (Brinkley et al, 1964;Anderson et al, 1967;Cook et al, 1967). It was not until recently that our group (Parvizi et al, 1976) found a very peculiar relationship between prepartal circulating LH and progesterone levels (Fig. 1).…”
Section: Late Gestationmentioning
confidence: 64%
“…41 to 17 hrs before parturition, however, progesterone values fluctuated erratically on a lower level and were independent of the still present LH episodes. This effect is likely to start earlier than 48 hrs prior to parturition, since there is general agreement, that progesterone has commenced its decline by then (Killian et al, 1973;Molokwu and Wagner, 1973;Robertson and King, 1974;Baldwin and Stabenfeldt, 1975;Parvizi et al, 1976).…”
Section: Late Gestationmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of LH in early and mid-pregnancy are similar to those observed in the mid-luteal phase of the oestrous cycle (Ziecik et al, 1982(Ziecik et al, /1983 (Parvizi etal, 1976;Kraeling etal, 1992). In miniature pigs, ovariectomy during the follicular phase, and ovariectomy on day 100 of pregnancy followed by abortion, result in a similar increase in LH secretion (Parvizi et al, 1976). Taken together, these results strongly suggest that high concentrations of progesterone inhibit LH pulsatility throughout pregnancy and that high concentrations of oestrogens amplify this inhibition during the last month of pregnancy.…”
Section: Introductionmentioning
confidence: 61%